Studi Kualitatif: Pengalaman Ibu Bersalin Dengan Metode Water Birth Di RS Happy Land Yogyakarta - Rahayu, Nova Avianti; Eugenius Phyowai Ganap; Farida Kartini (As-Shiha: Jurnal Kesehatan, 2022)
Labor is one of the most important events in a woman's life that can cause pain and stress (Kv, Raddi & Metgud, 2010). Water birth is a method of childbirth by using a medium of warm air that can reduce the feeling of labor and provide a sense of comfort (Meyer et al., 2010). Hunting experience has long-term implications for women's health and well-being. A negative birth experience can have an impact on women's health and development on birth (Smarandache et al., 2016). The aim of this research to describe women´s experiences of giving birth in water. The method using A Qualitative research method by studying phenomenology. Researchers conducted in-depth interviews with 6 key informants (mothers giving birth with the water birth method). The process of triangulation to 6 main informants (3 key main informants) and 3 additional informants (Midwives). The research instrument has been carried out expert judgment for 2 experts. The result is the benefits of water birth are reducing labor pain, providing relaxation during labor, protecting the privacy of labor and providing a positive delivery experience. The risks of water birth are infection, postpartum hemorrhage, water aspiration and hypothermia. The conclusion is mothers with water birth method have a positive delivery experience